Rational design of red-shifted 1,2-azaborinine-based molecular solar thermals - Müller, Adrian J.; Markhart, Johannes; Bettinger, Holger; Dreuw, Andreas (Chemical communications, 2025)
Rational computational design yields push-pull 4,5-substituted 1,2-azaborinines as molecular solar thermals with improved light harvesting. - , - 1,2-Azaborinines are a promising molecular class for application as molecular solar thermal (MOST) systems offering a solution for solar energy storage. Our computational screening of 4,5-substituted derivatives using density functional theory targeting excitation and storage energies revealed push-pull systems with significantly red-shifted absorption bands, enhancing their spectral overlap with the solar spectrum. Among these, the 4-cyano-5-hydroxy derivative, with a 1.1 eV red-shift of the first excited state compared to the unsubstituted molecule, was investigated in detail and was shown to retain the favourable properties of the parent system. It is thus particularly well suited as a MOST system.
Gesehen am 25.08.2025